The letter before the spirit : the importance of text editions for the study of the reception of Aristotle - Oppenraaij, Aafke M. I. van.; Fontaine, Resianne, 1953- (Aristoteles Semitico-Latinus, 2013)
The Letter before the Spirit contains original articles based on the papers given at the Huygens ING (The Hague, 2009) on the importance of text editions for the study of the transmission of Aristotle's works in the Semitico-Latin translations and their commentary tradition in the medieval world. Authors underline this importance in general overviews and theoretical outlines and present their own work on various text editions, ranging from Syriac and Arabic to Hebrew and (Graeco) Latin, and from Aristotle, Avicenna and Averroes to Plotinus, Michael Scot, William of Moerbeke, Judah ha-Kohen, Barhebraeus and Albertus Magnus. Editors are further encouraged to cross boundaries between disciplines and study the translation tradition of Aristotle's works in its entirety.